2021
DOI: 10.3390/geosciences11050208
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Crenulate Bay Profiles from Wave Fronts: Numerical Experiments and Empirical Formulae

Abstract: For crenulate-shaped bays, the coastal outline assumes a specific shape related to the predominant waves in the area: it generally consists of a tangential zone downcoast and a curved portion upcoast. Many coastal engineers have attempted to derive an expression of the headland bay shapes that emerge when a full equilibrium is reached (stable or dynamic). However, even though models for static equilibrium bays exist, they are merely of an empirical kind, lacking further insight on relationships between inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
2
2
0
Order By: Relevance
“…A substantial improvement in the predictive performance of the indirect sea wave estimations obtained in the present study case can be reached by combining them with the most advanced methods for the quantitative assessment of stochastic uncertainty propagation [65][66][67][68][69][70][71][72], as reported by previous environmental and ecohydraulic engineering studies [73][74][75][76][77][78][79][80]. Finally, as illustrated in Figure 6, in this study, a good correlation was observed between average buoy-based and average satellite-based wave heights (m) over the southern coasts of the Caspian Sea, associated with a slight overestimation in all the examined months.…”
Section: Comparative Analysissupporting
confidence: 60%
See 1 more Smart Citation
“…A substantial improvement in the predictive performance of the indirect sea wave estimations obtained in the present study case can be reached by combining them with the most advanced methods for the quantitative assessment of stochastic uncertainty propagation [65][66][67][68][69][70][71][72], as reported by previous environmental and ecohydraulic engineering studies [73][74][75][76][77][78][79][80]. Finally, as illustrated in Figure 6, in this study, a good correlation was observed between average buoy-based and average satellite-based wave heights (m) over the southern coasts of the Caspian Sea, associated with a slight overestimation in all the examined months.…”
Section: Comparative Analysissupporting
confidence: 60%
“…A substantial improvement in the predictive performance of the indirect sea wave estimations obtained in the present study case can be reached by combining them with the most advanced methods for the quantitative assessment of stochastic uncertainty propagation [65][66][67][68][69][70][71][72], as reported by previous environmental and ecohydraulic engineering studies [73][74][75][76][77][78][79][80].…”
Section: Comparative Analysissupporting
confidence: 59%
“…Hybrid approaches, also called one-line shoreline models in ref. 5 , couple oceanographic forcing with the morphological response of the beach 5,[19][20][21][22][23] . While these approaches vary in their level of simpli cation and the physical processes they describe, they generally: i) resolve the propagation of deep-water waves to the shore; ii) use the nearshore wave regime to estimate potential sediment transport rates; and iii) compute shoreline planform using transport rates and the continuity equation.…”
Section: Main Textmentioning
confidence: 99%
“…Most notably, the equivalent direction parameter (equal to the LDR null point) is of significant importance in shoreline evolution forecast, as it is nothing but the dominant direction of wave climate that persistently affects and sculpts the shoreline over years. In practical coastal engineering, the total wave climate is in fact seldom reduced to the equivalent wave component in midlong-term analysis of shoreline evolution, a procedure that has been widely applied in the literature, particularly in the field of static equilibrium crenulated bays [17]. One of the major findings concerning the LDR concept [3] is that, in terms of littoral drift, the effects of a deep-water wave climate can be equated to a single equivalent wave component, with parameters H s0,eq , T p0,eq , and α 0,eq , i.e.,…”
Section: Littoral Drift Rose Concept and Shore Diffusivitymentioning
confidence: 99%